The Curvilinear Relationship Between Start-Up Age and Host Growth on Sharing Accommodation Platforms - Xu, Zhen; Tang, Li; Yu, Xintao (Frontiers in Psychology, 2022)
The tourism and accommodation industry has long been a fertile field for digital entrepreneurial activities. However, sharing accommodation entrepreneurs have been ignored, whether in digital entrepreneurship or the sharing economy. This empirical study explored the relationship between start-up age and host growth based on the entrepreneurship learning theory to bridge the gap. In total, 348 hosts’ balanced panel data for 5 years were collected from the Airbnb platform. The results shown that (1) there was a curvilinear (inverted U-shaped) relationship between start-up age and host growth; (2) a critical primary growth strategy (product supply) significantly moderated the curvilinear relationship such that the inverted U-shaped relationship is less pronounced when the level of product supply is high. This study is helpful to understand digital entrepreneurs in the sharing accommodation and offers management suggestions for host growth.